Parent Support Relationship with Smoking Behavior - Andrianto, Muhammad Bagus; Nirbito, Mochamad Anom; Padila, Padila; Andri, Juli (JOSING: Journal of Nursing and Health, 2023)
This study aims to determine the relationship between parental support and school children's smoking behavior. This research method uses descriptive correlational research with a cross-sectional approach. The study's results based on class and age showed that 22 students, with a percentage of 73.3%, had supportive parental social support, and 16 students, with a rate of 53.3%, had terrible smoking behavior. The P value of parents' social support with smoking behavior is 0.207. In conclusion, it shows no relationship between parental consent and school children's smoking behavior. Keywords: Parents' Social Support, Smoking Behavior, Elementary School Students